Threats and Interventions on Wellbeing in Asylum Seekers in the Netherlands: A Scoping Review - Pluck, Ferdy; Ettema, Roelof; Vermetten, Eric (Frontiers in Psychiatry, 2022)
Abstract Background: Most asylum seekers experiences stress, not only due to the reason of fleeing and their travel, but also due to their compulsory stay in the asylum seeker center in the Netherlands and the asylum procedure. This often leads to self-medication and addiction which causes a lower self-esteem and lower quality of life. Adverse life events, forced migration and the prolonged asylum procedures, in addition to the complexity of the acculturation process can all contribute to higher levels of psychopathology. Objective: What are threats to well-being in terms of mental health, psychosocial and addiction problems and what are effective interventions for well-being for asylum seekers in asylum seeker centers in the Netherlands, reported in literature? Method: Following the descriptive nature of the research question and the need for identifying knowledge gaps, an overview of existing knowledge was created by executing a scoping review on influencing factors on mental health of asylum seekers. The Neuman Systems Model was used as a guiding framework to understand the complexity of the issues this population experience, and identifying the stressors and the factors which cause the imbalance and therefore the disease. Results: The literature review resulted in 26 articles that met the criteria for inclusion. The threats included, the influence of staying in the environment of an asylum seekers center, drug abuse among asylum seekers, health care professionals and employees who do not detect or underestimate the underlying suffering of asylum seekers, frequent relocations of asylum seekers. The two assessment instruments used were the Rapid-Assessment-Response-method (RAR-method) and the Health Information Assessment Tool Asylum Seeker tool (HIATUS-tool). Finally the five interventions identified, therapy for asylum seekers diagnosed with Post Traumatic Stress Disorder (PSTD), art therapy, education focused on prevention as intervention, cultural interview, and Mindspring. Conclusions: The knowledge on identifying and reducing threats, and assessment, and treatment interventions for asylum seekers living in an asylum seekers center found in the literature provided perspectives on improving their well-being. The great diversity of cultural aspects and continuous changes of the number and origin of refugees in the Dutch asylum seekers centers disrupted the continuity of care.